Pemahaman Kontekstual Atas Hadis Mahram Dalam Kutub Al-Tis'ah - Suryadinata, Ahmad Alfikri (Musawa Jurnal Studi Gender dan Islam, 2010)
The circulation of a hadits prohibiting women from travelling without a mahram has been understood as to oblige women to have a mahram companion whenever they travel. The inclusion of mahram in the concept of women traveling during the Prophet time was concerned with the comfort and safety of women during the jumey. The hadits was said as a precaution from the prophet to the danger women might face in the desert and as a token of appreciation to women's position in their social context of the age. As time goes by, the social situation of roads and journey has also changed. Now we do have many rules and regulations that guarantee the safety of women and men. Such contextual understanding of the purpose of mahram has actually been propagated by Imam Al-Syafi'I who didn't require the presence of mahram in traveling.